BIOMETRICS AUTHENTICATION METHODS - Gacovski, Zoran (ARCLER Press, 2020)
Biometrics Authentication Methods deals with the methods and approaches of biometrics and the fundamental principles involved in the hand shape biometrics. It consists of modern trends involved in the techniques related to biometrics and their evaluation. This book also discusses about strategies for exploiting independent cloud implementations of biometric experts in multibiometric scenarios, performance evaluation of automatic speaker recognition techniques for forensic applications, an AFIS candidate list centric fingerprint likelihood ratio model based on morphometric and spatial analyses (MSA), a new scheme for the polynomial based biometric cryptosystems and secure telemedicine: biometrics for remote and continuous patient verification.